Review of the commonly used colour vision testing methods - Mathebula, S. D . (SA Ophthalmology Journal, 2022)
Colour is an extremely important component of the information that people gather with their eyes. Most people use colour so automatically that they fail to appreciate how important it is in daily activity. Colour vision is perceived through three types of cones in the retina which are sensitive to red, green and blue colours. The purpose of this paper is to review the available and significant clinical colour vision tests in light of the need in the clinical examination of both congenital and acquired colour vision deficiency (CVD) and colour blindness. The tests are grouped and described as pseudoisochromatic plates, arrangement or matching tests, the lantern test and the anomaloscope test. The performance of each test type is described. When an individual exhibits CVD, the ability to discriminate cones diminishes under specific circumstances that could involve limitations in career choices, early education, academic, and everyday activities. Clinicians should test the colour vision of all patients with the Ishihara test. Those shown to have CVD should be evaluated with the Farnsworth D-15 and/or anomaloscope. Although there are many colour vision tests, their performances are difficult to compare. Once the results are obtained, appropriate advice should be given to the patient.
Journal article published in SA Ophthalmology Journal
Keywords: Anomaloscope; Colour vision; Colour vision deficiency; Farnsworth D-15 colour test; Ishihara test; Retina; Retinal degeneration; Color vision; Color vision -- Testing